Examining the Role of Attention Deficits in the Social Problems and Withdrawn Behavior of Children With Sluggish Cognitive Tempo Symptoms - Yung, Trevor W. K.; Lai, Cynthia Y. Y.; Chan, Jacob Y. C.; Ng, Shamay S. M.; Chan, Chetwyn C. H. (Frontiers in Psychiatry, 2021)
Previous studies have found that sluggish cognitive tempo (SCT) symptoms are often associated with social problems and withdrawn behavior. However, the possible neuropsychological mechanism underlying this relationship remains unclear. Some studies have also found that SCT symptoms are related to deficits in sustained attention and selective attention. However, no study has examined whether attention deficits are related to social problems and withdrawn behavior in children with SCT. This study was the first to examine the neuropsychological correlates of social problems and withdrawn behavior among children with SCT symptoms. The results showed that sustained attention measure (omission) predicted the severity of social problems and withdrawn behavior in children with SCT even after controlling for symptoms of attention-deficit hyperactivity disorder. Selective attention measure (response latency mean) was also found to predict the severity of social problems. These results suggest that the social problems commonly exhibited by children with SCT are related to deficits in sustained attention and attentional control. Thus, our results provide an initial support to the link between attention deficits and social problems among children with SCT.